DNA i-motif provides steel-like tough ends to chromosomes. Issue 1621 (2014) - Singh, Raghvendra P.; Blossey, Ralf; Cleri, Fabrizio
ABSTRACT: We studied the structure and mechanical properties of DNA i-motif nanowires by means of molecular dynamics computer simulations. We built up to 230 nm-long nanowires, based on a repeated TC5 sequence from NMR crystallographic data, fully relaxed and equilibrated in water. The unusual C●C+ stacked structure, formed by four ssDNA strands arranged in an intercalated tetramer, is here fully characterized both statically and dynamically. By applying stretching, compression and bending deformations with the steered molecular dynamics and umbrella sampling methods, we extract the apparent Young's and bending moduli of the nanowire, as well as estimates for the tensile strength and persistence length. According to our results, i-motif nanowires share similarities with structural proteins, as far as their tensile stiffness, but are closer to nucleic acids and flexible proteins, as far as their bending rigidity is concerned. Curiously enough, their tensile strength makes such DNA fragments tough as mild steel or a nickel alloy. Besides their yet to be clarified biological significance, i-motif nanowires may qualify as interesting candidates for nanotechnology templates, due to such outstanding mechanical properties.